Evaluasi Pelaksanaan Program Pengendalian Penyakit Demam Berdarah Dengue di Puskesmas Sikumana Kota Kupang - Stefania Delianti Cibolin; Serlie K.A. Littik; Dominirsep O. Dodo (Yayasan Literasi Sains Indonesia, 2026)
Dengue Hemorrhagic Fever (DHF) remains a public health concern in Kupang City, particularly in the working area of Sikumana Community Health Center (Puskesmas), which recorded 23 cases and 1 death in 2023, 46 cases in 2024, and 18 cases in 2025. This study aimed to evaluate the implementation of the Dengue Hemorrhagic Fever Prevention and Control Program (P2DBD) at Sikumana Puskesmas. A qualitative descriptive method with a case study approach was employed, utilizing in-depth interviews and documentation involving four informants. Data analysis was conducted through the stages of data collection, reduction, presentation, and conclusion drawing. The results revealed that the input components were reasonably adequate, including sufficient and well-trained human resources, as well as methods aligned with the Ministry of Health guidelines. However, infrastructure remained incomplete, notably the absence of fogging machines and limited abate stock. Funding was sourced from the Health Operational Assistance (BOK) allocated for abate procurement, fogging, and transportation. Regarding the process aspect, program implementation was not yet optimal, as indicated by suboptimal fogging activities, low community participation in larval nest eradication (PSN), insufficient understanding of abate usage, and address-related obstacles hindering epidemiological investigations. Program outputs also fell short of targets, with the Larva-Free Rate (ABJ) below 95% and household PSN coverage below 90%. Overall, the implementation of the P2DBD program was considered reasonably good; however, its effectiveness has not been fully achieved. Improvements are needed in community education, PSN monitoring, abate availability, as well as data management and cross-sector coordination.